2018
DOI: 10.3390/app8101717
|View full text |Cite
|
Sign up to set email alerts
|

Live Load Distribution Factors for Skew Stringer Bridges with High-Performance-Steel Girders under Truck Loads

Abstract: Because the methods used to compute the live load distribution for moment and shear force in modern highway bridges subjected to vehicle loading are generally constrained by their range of applicability, refined analysis methods are necessary when this range is exceeded or new materials are used. This study developed a simplified method to calculate the live load distribution factors for skewed composite slab-on-girder bridges with high-performance-steel (HPS) girders whose parameters exceed the range of appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The results of studies carried out by Hughs & Idriss [13] showed that LLDFs calculated by the equations given in AASHTO are conservative compared to the results of FE analyses. More recently, research on LLDF has considered specific bridge systems with longitudinal beams [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies carried out by Hughs & Idriss [13] showed that LLDFs calculated by the equations given in AASHTO are conservative compared to the results of FE analyses. More recently, research on LLDF has considered specific bridge systems with longitudinal beams [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Box girder is an important type of bridge structure. For box girder, many scholars have conducted research on shear lag, effective width [1][2][3][4][5], and live load distribution factors [6][7][8].…”
Section: Introductionmentioning
confidence: 99%